The Role of Pancasila Education in Shaping Democratic Awareness of Class X Students of SMKN 1 Sampang - Fendi Pradana; Sahrul Muzekki; Linda Ramadhanty Januar (Edukasi, 2026)
Pancasila Education plays a strategic role in fostering democratic awareness among students, particularly at the vocational high school level. This study aims to empirically analyze the role of Pancasila Education learning in shaping the democratic awareness of tenth-grade students at SMKN 1 Sampang. The research employed a descriptive quantitative approach using a survey method involving 68 respondents, consisting of 36 students from the Fabrication Engineering Department (TF 2) and 32 students from the Electronics Engineering Department (TE). The findings indicate that the majority of students demonstrate a good understanding of democratic principles, citizens’ rights and obligations, as well as the importance of deliberation in decision-making processes. However, students’ participation in democratic activities outside the school environment remains relatively low, indicating a gap between theoretical understanding and practical implementation. Discussion-based learning, simulations, and case studies were found to be more effective in enhancing students’ democratic awareness compared to conventional lecture methods. On the other hand, the study also identified several challenges, including limited instructional time, inconsistent implementation of interactive learning methods, and the influence of social media that is not yet adequately balanced with sufficient digital literacy skills. Therefore, strengthening participatory learning strategies and systematically integrating digital media literacy into the learning process are necessary to optimize the development of students’ democratic awareness